2014
DOI: 10.2139/ssrn.2464472
|View full text |Cite
|
Sign up to set email alerts
|

Structural Labor Supply Models and Wage Exogeneity

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…Haan (2004), Beninger et al (2007), Kornstad and Thoresen (2007), Bloemen (2010), Breunig and Gong (2010), Blundell and Shephard (2012), Löffler et al (2013), Aaberge and Colombino (2013), Kabátek et al (2014) and Dagsvik et al (2014)). It is quite intuitive that labour decisions are constrained on the choices of jobs and working hours, and then we prefer a discrete rather than a continuous labour supply model.…”
Section: The Unitary Discrete Choice Modelmentioning
confidence: 99%
“…Haan (2004), Beninger et al (2007), Kornstad and Thoresen (2007), Bloemen (2010), Breunig and Gong (2010), Blundell and Shephard (2012), Löffler et al (2013), Aaberge and Colombino (2013), Kabátek et al (2014) and Dagsvik et al (2014)). It is quite intuitive that labour decisions are constrained on the choices of jobs and working hours, and then we prefer a discrete rather than a continuous labour supply model.…”
Section: The Unitary Discrete Choice Modelmentioning
confidence: 99%
“…14 We also find similar patterns when looking separately at hour-wage elasticities (correlation of −.59 with observation years) and participation-wage elasticities (correlation of −.54) for married women. 15 Further potentially important factors are the treatment of wages in the estimation procedure (Löffler et al 2014) and the choice of the reference tax system for the benchmark. 16 Note that-like all meta-regressions-our analysis is not identifying causal effects since one can think of several potentially omitted variables.…”
Section: Endnotesmentioning
confidence: 99%
“…17 Note that we cannot include all possible aspects of model specification in our paper since there are too many dimensions and to few observations. For example, Löffler et al (2014) investigate the role of the treatment of wages for the size of elasticities. In order to do this, the authors estimate 3500 elasticities using a discrete-choice framework with all possible permutations of model choices.…”
Section: Endnotesmentioning
confidence: 99%
“…The similarity of the results of these two specifications is consistent with that provided by Löffler et al . (), who ran a meta‐analysis and found that the estimated elasticities are robust to the specification of the utility function …”
Section: Resultsmentioning
confidence: 99%
“… See Löffler et al . () for details on the assumptions and variations of discrete‐choice models of household labour supply. Another type of structural model is based on Hausman's () design and assumes a linear labour supply function. …”
mentioning
confidence: 99%